Escaping Kakania - Mrázek, Jan (Central European University Press, 2024)
Escaping Kakania is about fascinating characters—soldiers, doctors, scientists, writers, painters—who traveled from their eastern European homelands to colonial Southeast Asia. Their stories are told by experts on different countries in the two regions, who bring diverse approaches into a conversation that crosses disciplinary and national borders. The 14 chapters deal with the diverse encounters of eastern Europeans with the many faces of colonial southeast Asia. Some essays directly engage with post-colonial studies, contributing to an ongoing critical re-evaluation of eastern European “semi-peripheral” (non-)involvement in colonialism. Other chapters disclose a range of perspectives and narratives that illuminate the plurality of the travelers’ positions while reflecting on the specificity of the eastern European experience. The travellers moved—as do the chapter authors—between two regions that are off-centre, in-between, shiftingly “Eastern,” and disorientingly heterogeneous, thus complicating colonial and postcolonial notions of “Europe,” “East,” and East-West distinctions. Both at home and overseas, they navigated among a multiplicity of peoples, “races,” and empires, Occidents and Orients, fantasies of the Self and the Other, adopting/adapting/mimicking/rejecting colonialist identities and ideologies. They saw both eastern Europe and southeast Asia in a distinctive light, as if through each other—and so will the readers of Escaping Kakania.